Meeting report: Food Industries for People and Planet: Towards a new research agenda - International Food Policy Research Institute; Centre for European Policy Studies; KU Leuven Public Governance Institute; van Rheenen, Teunis; Vos, Rob (International Food Policy Research Institute, 2019)
Strong partnerships – encompassing organizations and stakeholders from around the world – will form the core of Food Industries for People and Planet (FIPP). This roundtable event served to establish a European Chapter of the FIPP Consortium by bringing together key European research institutes working on food systems and food industries with representatives of major food companies, government agencies, and development agencies. The European Chapter of the FIPP Consortium will engage with ongoing food policy and development cooperation debates for reshaping food systems in Europe and developing countries. The European Chapter will engage with the broader FIPP Consortium so that all stakeholders can jointly benefit from synergies and work together to identify priority research topics and develop a funding strategy.